A new bound for the distance to singularity of a regular matrix pencil. Issue 1 (15th March 2018) - Berger, Thomas; Gernandt, Hannes; Trunk, Carsten; Winkler, Henrik; Wojtylak, Michał
Abstract: For regular matrix pencils 𝒜( s ) =  sE  −  A the distance to the nearest singular pencil in the Frobenius norm of the coefficients is called the distance to singularity. We derive a new lower bound for this distance by using the spectral theory of tridiagonal Toeplitz matrices. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)